Population dynamics and games of variable size - Hansen, Matheus (2024)
Funding Information: FACCC and MH thanks C. Gokhale for suggesting applying the ideas from Chalub and Souza (2019) to a non-fixed number of players. This idea is at the origin of the present work. MH and FACCC are funded by national funds through the FCT \u2013 Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia , I.P., under the scope of the projects UIDB/00297/2020 ( https://doi.org/10.54499/UIDB/00297/2020 ) and UIDP/00297/2020 ( https://doi.org/10.54499/UIDP/00297/2020 ) (Center for Mathematics and Applications). FACCC also acknowledges the support of the project Mathematical Modelling of Multi-scale Control Systems: applications to human diseases 2022.03091.PTDC ( https://doi.org/10.54499/2022.03091.PTDC ), supported by national funds (OE), through FCT/MCTES . (CoSysM3). MH and FACCC contributed equally to the development of the work\u2019s ideas, computational codes, data analysis, discussions, and writing of the final version of the manuscript. We also thank both referees for many suggestions that helped to improve this work, and Renata Ramalho (Universidade NOVA de Lisboa) for helping in the language editing of the manuscript. Funding Information: FACCC and MH thanks C. Gokhale for suggesting applying the ideas from Chalub and Souza (2019) to a non-fixed number of players. This idea is at the origin of the present work. MH and FACCC are funded by national funds through the FCT \u2013 Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia, I.P. under the scope of the projects UIDB/00297/2020 ( https://doi.org/10.54499/UIDB/00297/2020) and UIDP/00297/2020 ( https://doi.org/10.54499/UIDP/00297/2020) (Center for Mathematics and Applications). FACCC also acknowledges the support of the project Mathematical Modelling of Multi-scale Control Systems: applications to human diseases 2022.03091.PTDC ( https://doi.org/10.54499/2022.03091.PTDC), supported by national funds (OE), through FCT/ MCTES. (CoSysM3). MH and FACCC contributed equally to the development of the work's ideas, computational codes, data analysis, discussions, and writing of the final version of the manuscript. We also thank both referees for many suggestions that helped to improve this work, and Renata Ramalho (Universidade NOVA de Lisboa) for helping in the language editing of the manuscript. Publisher Copyright: © 2024 The Authors